Effect of reading strategies, questioning, answering combined with think pair share against metacognitive skills, cognitive learning outcomes and retention - Hetharia, Monica; Corebima, Aloysius Duran; Gofur, Abdul (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2024)
The tendency of Natural Science Learning, especially biology today is students only studying biology as a product, memorize concepts, theories and laws. Facts in the field also found that teachers have not empowered the students' potential. Consequently metacognitive skills, cognitive learning outcomes, and low student retention. It takes a learning model that can improve and empower the students' potential. The application of Reading Questioning Answering learning strategies combined with Think Pair Share may increase metacognitive skills, cognitive learning outcomes, and student retention.This study used a quasi-experiment approach (quasi experimental) with a design of non-equivalent pretest-posttest control group design. The research was conducted in the second semester of the academic year 2014/2015 at the high school level in the city of Ambon. The application on the three schools was as follows: SMA N 4 Ambon: RQA, SMA N 5 Ambon: RQA combined with TPS, SMAN 14 Ambon: conventional.The results showed that there is influence of RQA combined with TPS learning model against metacognitive skills, there is the influence of RQA combined with learning model of TPS against cognitive learning outcomes, but there is no influence of RQA combined with learning model of TPS on the retention of students.